Effects of Ad Libitum Low Carbohydrate Versus Low Fat Diets on Body Weight and Fat Mass - Schick, Alex (Curr Dev Nutr, 2020)
OBJECTIVES: To describe the effects of ad libitum low-fat (LF) and low-carbohydrate (LC) diets on body weight and fat mass. METHODS: Sixteen adults without diabetes spent 29 continuous days residing at the Metabolic Clinical Research Unit of the NIH Clinical Center where they were fed ad libitum either an animal-based, LC diet (75% fat, 10% carbohydrates, 15% protein) or a plant-based, LF diet (75% carbohydrates, 10% fat, 15% protein). Participants were randomly assigned to one diet for the first phase of the study (14 days), after which they were switched to the other diet for the remainder of the study. Participants were given three meals daily and were provided with additional snacks amounting to 200% of their daily energy requirements as determined by their resting energy expenditure multiplied by 1.6. Subjects were told that this was not a weight loss study and were not informed about the primary study aim. They were instructed to eat as much or as little as they desired. Total body weight and fat mass were measured using a calibrated scale and dual-energy X-ray absorptiometry, respectively. Subjects were blinded to their data and wore loose-fitting scrubs to avoid any feedback regarding changes in the fit of their clothing. RESULTS: Subjects included 7 women and 9 men, with an age of (mean ± SE) 29 ± 1.7 years and BMI of 27.5 ± 1.5 at baseline. Participants lost weight on both diets, with the LC diet resulting in 1.34 ± 0.31 kg of weight loss (P = 0.0006) and the LF diet resulting in 1.09 ± 0.31 kg of weight loss (P = 0.003) which was not significantly different from the LC diet (P = 0.58). However, participants lost 0.6 ± 0.17 kg of body fat on the LF diet (P = 0.002) but the LC diet did not result in significant body fat loss (0.04 ± 0.17 kg; P = 0.8) and the difference in body fat loss between the diets was statistically significant (P = 0.03). CONCLUSIONS: While participants lost similar amounts of weight on both diets, only the LF diet led to significant body fat loss. Early weight loss with a LC diet does not necessarily reflect a similar state of negative energy balance as compared with a LF diet. FUNDING SOURCES: Intramural Research Program of the National Institutes of Diabetes and Digestive and Kidney Diseases.